Devising a Knowledge Culture - Gaur, Nishant; Gupta, Dr. Vikas (The journal of contemporary issues in business and government, 2021)
Purpose: The paper aims to explore the literature on culture facilitating knowledge management (KM) in an organisation. The paper deliberates on various attributes, components, framework and classification of culture that stimulates KM. Design/methodology/approach: A systematic review of peer-reviewed journal articles has been carried out to understand the culture that fosters KM from Pro-Quest, Emerald and EBSCO host. Various attributes, components, framework and classification of culture have been extracted from the literature that impacts KM processes, knowledge assets, Knowledge conversion cycles and types of knowledge sharing. Findings: The literature reveals a positive impact of cultural attributes, components of culture, various cultural frameworks and various classification of culture on KM processes, knowledge assets, knowledge conversion cycles and types of knowledge sharing. Research implications: This paper is an output of extensive literature review studying all the attributes, components, framework and classification of culture that impacts KM. However, it would have been better to go for a precise study deliberating on a particular dimension of culture amongst framework, attributes or classification which impacts a specific KM dimension amongst KM processes, knowledge assets, KM conversion cycle and types of knowledge sharing. Also, a longitudinal study would have given long term data to understand how organisational culture would have influenced KM. Research limitations: This paper is an output of extensive literature review studying all the attributes, components, framework and classification of culture that impacts KM. However, it would have been better to go for a precise study deliberating on a particular dimension of culture amongst framework, attributes or classification which impacts a specific KM dimension amongst KM processes, knowledge assets, KM conversion cycle and types of knowledge sharing. Also, a longitudinal study would have given long term data to understand how organisational culture would have influenced KM. Originality/value: This paper contributes to knowledge culture literature by adding the fact that culture not only affects human resource activities but also plays a prominent role in KM.